IMPLEMENTATON OF PHARMACEUTICAL CARE IN PORTUGAL, SIX YEARS AFTER - Sílvia Martins; Filipa Alves da Costa; Margarida Caramona (Formifarma, LDA., 2015)
Objectives: To evaluate the level of implementation of pharmaceutical care in Portugal; to characterize the pharmaceutical team, the infrastructures and the types of services offered by Portuguese pharmacies; to analyze the evolution of these indicators between 2006 and 2012. Study Type: Observational cross-sectional study. Location: Portuguese Community Pharmacies. Population: Community pharmacists practicing in Portugal. Methods: A cross-sectional study was used, where the Portuguese Pharmaceutical Society enabled the mailing of the questionnaire to all registered community pharmacists (n = 6797). The tool used for data collection was an adapted version of the Behavioral Pharmaceutical Care Scale, consisting of two sections. Section A characterized the pharmacy structure, resources (e.g. professionals), and services and section B evaluated the type of services provided to patients who last entered the pharmacy referring to a specific time period, referring to descriptions of varied situations. Results were processed using Statistical Package for the Social Sciences version 19.0. Results: 686 pharmacists responded to the questionnaire, representing a pharmacy response rate of 23,4%. The team comprised mostly pharmacists (M = 3 pharmacists, SD = 1,7; M = 2 technicians, SD = 1,5). The most common service offered was measurement of biochemical parameters, such as a blood pressure (99,9%) and glycaemia (99%). Worth noting the widespread implementation of new services, including nutrition (63,2%) and podiatry (40,7%) appointments. The Behavioral Pharmaceutical Care Scale score increased from 76,5 to 86,3 in the time period considered, indicating more offer of the pharmaceutical care service to the portuguese population. Conclusions: Data collected in this study shows recent legislative changes, including the introduction of Decree-Law no.307/2007 and Decree no.1429/2007, led to profound changes in the functioning of pharmacies.